The Influence of Applying English Songs to Improve Students’ Listening, Writing and Speaking - Heni Merina (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to find out the influence of applying English songs to improvestudents’listening, writingand speaking skillsat Poltekpar Palembang. What influence that embossed by English songs also will explain in this study. Through the qualitative method, the data gathered showed that English songs can improve listening, writing and speaking skill. Listening is one of skill in the English language that should be mastered, Writing is a technical skill that allows us to communicate effectively through the written word and Speaking is an activity to express oneself in a situation or to express a sequence of ideas among people in a community by using verbal and non-verbal symbols in a particular language, situation, and context. People who learn the English language should master three of them. To improve the skills, people can practicethroughEnglish songs because English songs have the benefit to improve listening, writing and speaking skills.